REFLEKSI KRITIS KONDISI DEMOGRAFI INDONESIA: ANTARA BONUS DAN BENCANA DEMOGRAFI - Sarmita, I Made (Universitas Pendidikan Ganesha, 2017)
Indonesia still has various demographic problems. Large population, low population quality, and uneven distribution of population. In quantity, Indonesia can be said will soon enjoy the demographic dividend because the large number of population is a productive age. But the large number of productive age population was not followed by a reliable quality and this can actually be a demographic disaster. This article presents the outlook as a critical reflection of Indonesia's current demographic condition derived from the review of demographic data and related writings. The results obtained are that the demographic conditions of Indonesia are in the